Mathematical Model for Human Resource Planning through Stochastic Processes (International Journal of Scientific Research and Management (IJSRM), 2017)
Two category organization subjected to random depart of personnel due to policy decisions taken by the organization is considered. we have found mathematical model and analytical results for the mean and variance of the time for employment at any organization